Steps Towards Alcohol Misuse Prevention Programme (STAMPP): a school- and community-based cluster randomised controlled trial - Harry Sumnall; Ashley Agus; Jon Cole; Paul Doherty; David Foxcroft; Séamus Harvey; Michael McKay; Lynn Murphy; Andrew Percy (NIHR Journals Library, 2017)
Background: Alcohol use in young people remains a public health concern, with adverse impacts on outcomes such as health, well-being, education and relationships. Objectives: To assess the effectiveness and cost-effectiveness of a combined classroom curriculum and parental intervention on self-reported alcohol use [heavy episodic drinking (HED)] and alcohol-related harms (indicators such as getting into fights after drinking, poorer school performance and trouble with friends and family). Design: A two-arm, cluster randomised controlled trial with schools as the unit of randomisation. Setting: A total of 105 post-primary schools in Northern Ireland (NI) and Glasgow/Inverclyde Educational Authority areas. Participants: A total of 12,738 male and female secondary school students (intervention delivered when students were in school year 9 in NI or S2 in Scotland in the academic year 2012-13 and aged 12-13 years) were randomised. Randomisation and baseline (T0) surveys took place when children were in school year 8 or S1. Schools were randomised (1 : 1) by an independent statistician to the Steps Towards Alcohol Misuse Prevention Programme (STAMPP) or to education as normal (EAN). All schools were stratified by free school meal provision. Schools in NI were also stratified by school type (male/female/coeducational). Interventions: STAMPP combined a school-based alcohol harm reduction curriculum [an adapted version of the School Health and Alcohol Harm Reduction Project (SHAHRP)] and a brief parental intervention designed to support parents in setting family rules around drinking. The classroom component comprised two phases delivered over 2 years, and the parental component comprised a standardised presentation delivered by a trained facilitator at specially arranged parent evenings on school premises. This was followed up a few weeks later by an information leaflet mailed to all intervention pupils' parents highlighting the main points of the evening. Main outcome measures: (1) Self-reported HED (defined as self-reported consumption of ≥ 6 units in a single episode in the previous 30 days for male students and ≥ 4.5 units for female students) assessed at 33 months from baseline (T3); and (2) the number of self-reported harms (harms caused by own drinking) assessed at T3. Data sources: Self-completed pupil questionnaires. Results: At final follow-up (T3), data were available for 5160 intervention and 5073 control pupils for the HED outcome, and for 5234 intervention and 5146 control pupils for the self-reported harms outcome. The intervention reduced self-reported HED compared with EAN (p < 0.001), but did not reduce self-reported harms associated with own drinking. The odds ratio for the intervention effect on HED was 0.596 (standard error 0.0596, 95% confidence interval 0.490 to 0.725). The mean cost of delivery per school was £818 and the mean cost per individual was £15. There were no clear cost savings in terms of service utilisation associated with the intervention. The process evaluation showed that the classroom component engaged and was enjoyed by pupils, and was valued by teachers. Schools, students, intervention trainers and delivery staff (teachers) were not blind to study condition. Data collection was undertaken by a team of researchers that included the trial manager and research assistants, some of whom were not blinded to study condition. Data analysis of primary and secondary outcomes was undertaken by the trial statistician, who was blinded to the study condition. Limitations: Although the classroom component was largely delivered as intended, there was very low attendance at the parent/carer event; however, all intervention pupils' parents/carers received an intervention leaflet. Conclusions: The results of this trial provide some support for the effectiveness and cost-effectiveness of STAMPP in reducing heavy episodic (binge) drinking, but not in reducing self-reported alcohol-related harms, in young people over a 33-month follow-up period. As there was low uptake of the parental component, it is uncertain whether or not the intervention effect was accounted for by the classroom component alone. Trial registration: Current Controlled Trials ISRCTN47028486. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 5, No. 2. See the NIHR Journals Library website for further project information. The Public Health Agency of NI and Education Boards of Glasgow/Inverclyde provided some intervention costs. Diageo provided funds to print some workbooks. The remaining intervention costs were internally funded.